Decolonizing Teaching and Classroom Experiences in Africa: The Role of Bilchiinsi - Ali Ahmed; Najat Ahmed; Amadu Musah Abudu (Educational Considerations, 2025)
This article is framed in decoloniality and responds to calls for educational systems, curricula, and classroom instruction in sub-Saharan Africa and other Global South contexts to be decolonized. The article proposes the adoption of a Dagbaŋ Indigenous philosophy—Bilchiinsi (ethical living)—as a relational pedagogy for transforming teaching and classroom interaction in Ghana and beyond. After a brief examination of decoloniality and associated concepts, the authors discuss Bilchiinsi within a decolonial framework, highlighting its epistemological, ontological, and axiological underpinnings. It concludes by considering the classroom as a potential space for practicing Bilchiinsi, addressing the possibilities and limitations of using it as a decolonizing pedagogy.
Keywords: Bilchiinsi philosophy; classroom experiences; decoloniality